Flowering and fruiting of woody plants in white-sand and clay forests in Peruvian Amazonia - Zárate, Ricardo (2006)
Patterns of flowering and fruiting of 176 species of woody plants in white-sand and clay forests near Iquitos, are presented. Observations were biweekly during a period of 12 months (April 2003 - March 2004). The study site were divided into 10 plots of 20 x 50 m, of which, 5 plots were established in each forest type. Flowering occurred most frequently from September to December, period in which there was an increase in precipitation. Similarly, there was a tendency for maximum fruiting from November to March. This period coincided with the season of greater precipitation (October-December), followed by a short interval period of less precipitation (January), ending in February, period of increased precipitation. Flowering lasted from 0,5 to 9 months and fruiting lasted from 1 to 10 months. In the clay forest, the flowering season showed its greater peak during the period with less rain (August-October), when 22,2% of the individuals were flowering. Whereas, in the white-sand forest, the greater peak of flowering occurred in the period of increased rain (November-December), with 19,3% of individuals flowering. On the other hand, the fruiting season in clay and white-sand forests showed two marked peaks. It tended to be greater during the rainiest period (February-March), with 20% and 23,5% of individuals, respectively, as well as during second highest rainy period (November-December) with 18,9% and 21% of individuals, respectively. The correlation index between the precipitation and temperature with the flowering and fruiting period were positive in both cases.